PELATIHAN PENINGKATAN EKONOMI KREATIF BUCKET SNACK DAN PEMASARAN DIGITAL MARKETING PADA IBU-IBU PKK DI DESA NGADIREJO KARANGANYAR - Widianto, Tri; Angelina, Yosephine; Panglipurningrum, Yofhi Septian; Octaviani, Andri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
Bucket snacks have become a unique business and gift that has started going viral in the millennial era and is loved by many people. The history of the snack bucket itself is closely related to the flower bucket. The business benefits obtained can increase creativity in innovating in business, becoming a promising business opportunity for someone who wants to have additional income, such as students, private employees, housewives or others. Digital Marketing is one of the marketing media that is currently in great demand by the public to support various activities carried out. With digital marketing, communication and transactions can be done at any time/real time and can be global or worldwide. With the large number of chat-based social media users, it is increasingly opening up opportunities for SMEs to develop their market in the grip of a smartphone. For community service this time, Service Team will conduct training. The training that will be carried out is making bucket snacks that have economic value and introducing their marketing through digital marketing.